Green Approaches to Carbon Nanostructure-Based Biomaterials - Simone Adorinni; Maria C. Cringoli; Siglinda Perathoner; Paolo Fornasiero; Silvia Marchesan (Applied Sciences, 2021)
The family of carbon nanostructures comprises several members, such as fullerenes, nano-onions, nanodots, nanodiamonds, nanohorns, nanotubes, and graphene-based materials. Their unique electronic properties have attracted great interest for their highly innovative potential in nanomedicine. However, their hydrophobic nature often requires organic solvents for their dispersibility and processing. In this review, we describe the green approaches that have been developed to produce and functionalize carbon nanomaterials for biomedical applications, with a special focus on the very latest reports.